A real-time decoding sequencing technology—new possibility for high throughput sequencing. Issue 64 (16th August 2017) - Pu, Dan; Xiao, Pengfeng
Abstract : The challenges and corresponding solutions for a decoding sequencing to be compatible with high throughput sequencing (HTS) technologies are provided. Abstract : A real-time decoding sequencing developed by our group offers long read length, high sequencing accuracy and high compatibility, making it have great potential in high throughput sequencing (HTS) platforms. Here, we first discuss its potential advantages in HTS in terms of read length, sequencing accuracy, and turnaround time. We then discuss its disadvantages including homopolymers and chain decoding mistakes. How to handle these two major disadvantages is also discussed with respect to resequencing and de novo sequencing. We also provide the characteristics of this technology for HTS in terms of error-correcting and discriminating SNP/deletion/insertion. Finally, the existing sequencing platforms with which this technology is compatible are discussed. This technology is not only compatible with the first-generation sequencing platform, but also the second-generation and even the third-generation sequencing platforms. It will further improve the advantages of existing sequencing platforms (read length of PGM and 454 system) and compensate some disadvantages of other next generation sequencing (NGS) platforms (sequencing accuracy of PGM sequencer). We fully hope it will provide a new promising technology for researchers and customers to extend applications of the current and upcoming platforms in almost every area in life and biomedical sciences.